Waterproof, Ultrahigh Areal‐Capacitance, Wearable Supercapacitor Fabrics. Issue 19 (24th February 2017) - Yang, Yu; Huang, Qiyao; Niu, Liyong; Wang, Dongrui; Yan, Casey; She, Yiyi; Zheng, Zijian
Abstract : High‐performance supercapacitors (SCs) are promising energy storage devices to meet the pressing demand for future wearable applications. Because the surface area of a human body is limited to 2 m 2, the key challenge in this field is how to realize a high areal capacitance for SCs, while achieving rapid charging, good capacitive retention, flexibility, and waterproofing. To address this challenge, low‐cost materials are used including multiwall carbon nanotube (MWCNT), reduced graphene oxide (RGO), and metallic textiles to fabricate composite fabric electrodes, in which MWCNT and RGO are alternatively vacuum‐filtrated directly onto Ni‐coated cotton fabrics. The composite fabric electrodes display typical electrical double layer capacitor behavior, and reach an ultrahigh areal capacitance up to 6.2 F cm −2 at a high areal current density of 20 mA cm −2 . All‐solid‐state fabric‐type SC devices made with the composite fabric electrodes and water‐repellent treatment can reach record‐breaking performance of 2.7 F cm −2 at 20 mA cm −2 at the first charge–discharge cycle, 3.2 F cm −2 after 10 000 charge–discharge cycles, zero capacitive decay after 10 000 bending tests, and 10 h continuous underwater operation. The SC devices are easy to assemble into tandem structures and integrate into garments by simple sewing. Abstract : A multiwall carbon nanotube/reduced graphene oxide composite fabric electrode with an ultrahigh areal capacitance of 6.2 F cm −2 is obtained by alternating filtration on Ni‐coated cotton fabric. With simple textile sewing and sealing techniques, these high‐performance electrodes are assembled into all‐solid‐state fabric‐type supercapacitor devices, which possess record‐breaking initial capacitance (2.7 F cm −2 ) and excellent retention, remarkable flexibility, and are waterproof.